Efek Hipoglikemik Kombinasi Infus D - GUNAWAN PAMUDJI WIDODO; RINA HEROWATI; BETA K. PRAMUDYAWARDHANI (Fakultas Farmasi Universitas Pancasila, 2012)
Talok (Muntingia calabura L.) leaf is a traditional medicinal plant which empirically used to treat diabetes mellitus. This research aimed to know hypoglycemic effect of combination dose of talak leaves infuse-metformin and glibenclamide on Na2EDTA induced-diabetic rats. Diabetic animal model were conducted by induction of Na2EDTA dose of 70 mg kg bw for 3 days. The test groups divided into six groups which were treated with: 50 mg kg bw CMC-Na suspension (negative control 1st group), 0.9 mg kg bw glibenclamide (2nd group), metformin 90 mg kg bb (3rd group), 900 mg kg bw talok leaves infuse (4th group), combination of talok leaves infuse-glibenclamide (450 mg : 0.45 mg/kg bw) (5th group), combination of talok leaves infuse-metformin (450 mg : 45 mg kg bw) (6th group). The levels of blood glucose were examined in all 6 experimental groups on day 0, 4th and 7th. The data obtained were analyzed by one way ANOVA (p < 0.05). The results showed that all of combination could decrease the blood glucose levels significantly. The combination treatment of talok leaves infuse-glibenclamide showed a higher hypoglycemic effect than either drug alone, while combination treatment of talok leaves infuse-metformin showed a similar hypoglycemic effect to either drug alone.